Effect of subdoses of sugarcane ripeners on lettuce physiology in a drift scenario - de Souza Rodrigues, Juliana [UNESP]; Ventura, Ricardo Borjas [UNESP]; da Silva Santos, Renata Thaysa [UNESP]; Bacha, Allan Lopes [UNESP]; Gratão, Priscila Lupino [UNESP]; Grey, Timothy Lane; da Costa Aguiar Alves, Pedro Luís [UNESP] (Springer Nature, 2021)
In order to understand the physiological effects of ripeners in sensitive crops, the objective of this work was to evaluate the effect of subdoses of the ripeners glyphosate, trinexapac-ethyl and sulfometuron methyl commonly used in sugarcane, in the growth of lettuce cultivar ‘Lucy Brown’ and ‘Vanda’. To address the effects of the products in the lettuce physiology, analyses of fresh weight, dry weight, number of leaves, chlorophyll content, quantum efficiency of photosystem II, lipid peroxidation (MDA), hydrogen peroxide (H2O2), glutathione reductase (GR), guaiacol peroxidase (GPOX) were performed. We observed that among the products tested, glyphosate had minor impact on plant growth, compared to trinexapac-ethyl and sulfometuron methyl. All products induced a decrease in chlorophyll content for both cultivars. Chlorophyll A fluorescence suffered a major reduction with trinexapac-ethyl and sulfometuron methyl in ‘Vanda’ and no differences were observed for ‘Lucy Brown’. MDA content and enzyme quantification varied by cultivar and the sugarcane ripener tested. By disturbing chlorophyll content and quantum efficiency of photosystem II, through these sugarcane ripeners did not have direct mode of action affecting photosystem II, they can cause some level of damage and activate different mechanisms and at different times, in response to stress. In this sense, it is possible to observe that reduced doses of glyphosate, trinexapac ethyl, and sulfometuron methyl affect the development of lettuce at different levels and trigger an oxidative response that was cultivar dependent.
Keywords: Enzymes; Oxidative stress; Photosynthesis; Plant growth regulators